High fat feeding is associated with stimulation of the hypothalamic-pituitary-adrenal axis and reduced anxiety in the rat. (February 2015) - McNeilly, Alison D.; Stewart, Caroline A.; Sutherland, Calum; Balfour, David J.K.
Highlights: Rats fed a high fat diet elicit anxiolytic-like behavior in an elevated plus maze. High fat diet (HFD) increases plasma corticosterone levels. Levels are elevated at baseline and following exposure to the elevated plus maze. Glucocorticoid receptor (GR) immunoreactivity is altered by HFD. HFD increases GR immunoreactivity in parietal cortex and hypothalamus. The effects of HFD on behavior do not correlate with corticosterone or GR changes. Summary: Previous studies have shown that diet-induced obesity is associated with insulin resistance and impaired feedback control of the hypothalamic-pituitary-adrenal (HPA) axis. The objective of this study was to test the hypothesis that hyper-secretion of glucocorticoid, evoked by feeding rats a high fat (HF) diet for 12 weeks, also influences behavioural and neural responses to the elevated plus-maze (EPM) test of anxiety. HF-fed animals exhibited anxiolytic-like behaviour in the EPM but were also hyperactive in this test. Covariant analysis established that the anxiolytic-like behaviour was not secondary to the increase in activity. The HF diet significantly increased basal levels of plasma corticosterone. The groups exposed to the EPM also displayed increased plasma corticosterone levels compared to the relevant control group, although the increment was smaller in the HF-fed animals. Glucocorticoid receptor (GR) immunoreactivity in the cytoplasmic fraction of parietal cortex and hypothalamus and the particulate fraction of the parietal cortex were increased by HF feeding. The behavioural changes evoked by HF feeding did not correlate significantly with changes in GR immunoreactivity in each treatment group or 5-HT turnover in the brain areas studied. It is concluded that anxiolytic properties evoked in the EPM by high fat feeding are unlikely to be related to the changes in HPA function seen in animals fed this diet.